(untitled) (AACINI - International Journal of Industrial Engineering, 2024)
The advancement of technology in recent years induces industries to adapt their processes to increasingly changing environments and to the demand for greater added value in products and services by their customers. While many organizations achieve an adequate growth rate, others need to make considerable changes to achieve it. The objective of this work is to identify points of improvement in the production processes of a multinational food company through the incorporation of Industry 4.0 technologies. Based on an initial technological diagnosis, Soft System Methodology is applied with the purpose of participatively detecting the main weaknesses of the process and designing an action plan to address them. In order to prioritize the actions outlined in the plan, the Hierarchical Analytical Process is implemented. The result is a plan to incorporate smart technologies that generates significant improvements in the production processes of the company under study, achieving a 35.47% reduction in man hours and optimizing the flow of information between areas. It is concluded that the proposed improvements allow the company to face a technological transformation process, improve the availability of key information for decision making and add value to operations throughout the supply chain.